Parietal lesions produce illusory conjunction errors in rats - Kesner, Raymond P. (Frontiers in Integrative Neuroscience, 2012)
When several different objects are presented, visual objects are perceived correctly only if their features are identified and then bound together. Illusory-conjunction errors result when an object is correctly identified but is combined incorrectly. The parietal cortex (PPC) has been shown repeatedly to play an important role in feature binding. The present study builds on a series of recent studies that have made use of visual search paradigms to elucidate the neural system involved in feature binding. This experiment attempts to define the role the PPC plays in binding the properties of a visual object that varies on the features of color and size in rats. Rats with PPC lesions or control surgery were exposed to three blocks of 20 trials administered over a 1-week period, with each block containing ten-one feature and ten-two feature trials. The target object consisted of one color object (e.g. black and white) and one size object (e.g. short and tall). Of the ten one feature trials, five of the trials were tailored specifically for size discrimination and five for color discrimination. In the two-feature condition, the animal was required to locate the targeted object among four objects with two objects differing in size and two objects differing in color. The results showed a significant decrease in learning the task for the PPC lesioned rats compared to controls, especially for the two-feature condition. Based on a subsequent error analysis for color and size, the results showed a significant increase in illusory conjunction errors for the PPC lesioned rats relative to controls for color and relative to color discrimination, suggesting that the PPC may support feature binding as it relates to color. There was an increase in illusory conjunctions errors for both the PPC lesioned and control animals for size, but this appeared to be due to a difficulty with size discrimination.